Localização de faltas em linhas de transmissão de múltiplos terminais a partir de registros oscilográficos sincronizados via transformada wavelet - Cruz, Melinda Cesianara Silva da (2010)
The electric energy is essential to the development of modern society and its increasing demand in recent years, effect from population and economic growth, becomes the companies more interested in the quality and continuity of supply, factors regulated by ANEEL (Agência Nacional de Energia Elétrica). These factors must be attended when a permanent fault occurs in the system, where the defect location that caused the power interruption should be identified quickly, which is not a simple assignment because the current systems complexity. An example of this occurs in multiple terminals transmission lines, which interconnect existing circuits to feed the demand. These transmission lines have been adopted as a feasible solution to suply loads of magnitudes that do not justify economically the construction of new substations. This paper presents a fault location algorithm for multiple terminals transmission lines - two and three terminals. The location method is based on the use of voltage and current fundamental phasors, as well as the representation of the line through its series impedance. The wavelet transform is an effective mathematical tool in signals analysis with discontinuities and, therefore, is used to synchronize voltage and current data. The Fourier transform is another tool used in this work for extract voltage and current fundamental phasors. Tests to validate the location algorithm applicability used data from faulty signals simulated in ATP (Alternative Transients Program) as well as real data obtained from oscillographic recorders installed on CHESF s lines.